Understanding the reactivity properties of Au-n (6 <= n <= 13) clusters using density functional theory based reactivity descriptors - De, Himadri Sekhar; Krishnamurty, Sailaja; Pal, Sourav (Journal of Physical Chemistry C, 2010)
{Relativistic density functional theory (DFT) based calculations have been performed on gold clusters with six to thirteen atoms (Au-n